Niger : Request for a New Three-Year Arrangement Under the Extended Credit Facility: Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Niger. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
Niger's medium-term fiscal policy aims to support the growth strategy by creating fiscal space for increasing development spending while maintaining external debt sustainability. Economic activity in recent years has been affected by large swings in agricultural production. The authorities' program is aimed at maintaining macroeconomic stability while increasing resilience to shocks; strengthening public finance and debt management; and supporting private and financial sector development. Medium-term fiscal policy will aim at maintaining debt sustainability while creating room for increased development spending.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet